2018
DOI: 10.1073/pnas.1810517115
|View full text |Cite
|
Sign up to set email alerts
|

A small single-domain protein folds through the same pathway on and off the ribosome

Abstract: In vivo, proteins fold and function in a complex environment subject to many stresses that can modulate a protein's energy landscape. One aspect of the environment pertinent to protein folding is the ribosome, since proteins have the opportunity to fold while still bound to the ribosome during translation. We use a combination of force and chemical denaturant (chemomechanical unfolding), as well as point mutations, to characterize the folding mechanism of the src SH3 domain both as a stalled ribosome nascent c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 53 publications
7
42
1
Order By: Relevance
“…The correlation between the three-state and two-state folding of variants in standard refolding experiments and their ability to read through the SecM stall implies that the intermediate observed in CD and HDX studies off the ribosome is likely populated on the ribosome and again suggests that the general folding trajectory, or pathway, of RNH* is unaltered on the ribosome. These data, together with the pulse proteolysis results, agree with studies of the folding mechanisms of other small proteins on the ribosome, which have shown that the folding trajectory does not change for RNCs relative to free proteins (5,11). Combining this pulse proteolysis approach with other site-specific mutations in a f-value analysis will further elucidate the folding pathway of ribosome-tethered RNH* I53D and could be applied to other nascent chains to characterize the effect of the ribosome on a range of folding mechanisms.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The correlation between the three-state and two-state folding of variants in standard refolding experiments and their ability to read through the SecM stall implies that the intermediate observed in CD and HDX studies off the ribosome is likely populated on the ribosome and again suggests that the general folding trajectory, or pathway, of RNH* is unaltered on the ribosome. These data, together with the pulse proteolysis results, agree with studies of the folding mechanisms of other small proteins on the ribosome, which have shown that the folding trajectory does not change for RNCs relative to free proteins (5,11). Combining this pulse proteolysis approach with other site-specific mutations in a f-value analysis will further elucidate the folding pathway of ribosome-tethered RNH* I53D and could be applied to other nascent chains to characterize the effect of the ribosome on a range of folding mechanisms.…”
Section: Discussionsupporting
confidence: 87%
“…This accounts for the observed decrease in stability for these RNCs. Although we can only sample a limited range of urea concentrations in these RNC experiments, the similarity in urea dependence (m ‡ unf) indicates the protein is traversing the same transition state barrier on and off the ribosome, consistent with observations for the small proteins titin and SH3 (5,11). Assuming that RNH* I53D folds in a two-state mechanism on the ribosome (populating only U and N), this implies that the presence of the ribosome does not affect the folding rate and suggests a mechanism by which the ribosome destabilizes the nascent chain by promoting its unfolding.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We attached DNA handles via thiol chemistry to two cysteines engineered at specific positions in the protein (see Methods) 13,14 . The handle position determines the direction and region of the protein subjected to the force applied through the optical tweezers (i.e., pulling geometry) [15][16][17] . We generated three PKA regulatory subunit constructs with unique pulling geometries to probe cAMP binding coupled to inter-domain interactions (Fig 1b, right).…”
Section: Landscape Parametersmentioning
confidence: 99%